Glandular Odontogenic Cyst: Report of 20 Cases and Review of Literature - Huh, Young-Sung; Oh, Kyu-Young; Yoon, Hye-Jung; Lee, Jae-Il; Hong, Seong-Doo (The Korean Journal of Oral and Maxillofacial Pathology, 2016)
The aim of this study was to present the clinical, radiological, and histopathological findings of 20 new Korean GOC cases with a brief literature review. The mean age of 20 GOC patients was 43.5 years (range, 29-73 years) with a strong predilection for male (male-to-female ratio, 4:1). Nine cases were located in the maxilla and 11 cases in the mandible. Eight cases involved the anterior areas of the jaws and 12 cases were located in the posterior area. Most of the cases (16/20, 80.0%) showed a well-defined unilocular radiolucency and some showed cortical perforation (55.6%) and bony expansion (72.2%) in computed tomography. The most common histopathological feature was eosinophilic cuboidal cells (100%), followed by clear cells (95.0%), mucous cells (85.0%), variations in thickness (85.0%), and intraepithelial microcysts (80.0%). All cases were surgically treated by enucleation and no recurrences were found in routine follow-up. KCI Citation Count: 0